PENGAJIAN KITAB BULU>G AL-MARA>M DALAM MAJLISUZZIKR BRUNEI DARUSSALAM: KAJIAN HADIS
ewline"> This article studies hadiths used in Majlisuzzikr led by Habib Abdul Hamid al-Mahdaly in Brunei Darussalam context. The object of this research is limited by investigating the recording video of the lectures on Bulūg alMarām, composed by Ibn ajar al-‘Asqalānī, that can be downloaded from cyberspace, you tube. However, the study of hadith there has a close relation with the government that put into effect the Islamic law (syariat). The existence of hadith study in this Majlis apparently is inclined to support the government of Sultan Hassanal Bolkiah. According to the Alfatih mapping of explanation (pensyarh